The Development of E-Learning Material of English for Tourism for Tourism Personnel in Labuan Bajo - Retnawati, Saptina; atmawijaya, tito dimas; kusumoriny, laksmy Ady (ELT-Lectura, 2024)
The purpose of this study was to create e-learning material of English for tourism personnel in Labuan Bajo. This study was a research and development one. The outcome of this research was learning devices in the form of module. This study refers to Borg and Gall’s development research procedure consisting collecting data, planning, product draft development, expert validation, revision, and field test. There were two kinds of data in this study; qualitative and quantitative data. The qualitative data was in the form of suggestions from validator regarding module, as well as the results of observation and interview. Meanwhile the quantitative data was obtained from the participant’s result of pretest and postest. The posttest results showed that there was an increase in scores of 37% from the participants' average scores. This showed that materials in the form of module were effective in improving the English language skills of tourism actors in Labuan Bajo. Apart from that, the material in the form of a module has met all the criteria in terms of content feasibility and presentment feasibility by validators who are experts in their fields. Keywords: E-learning, Material, English for Tourism, Tourism Personnel